Bell’s palsy after concomitant chemoradiotherapy: a case report and literature review - Choi, Sul Gi; Oh, Ji Seok; Myoung, Hoon; Seo, Mi Hyun (Journal of dental anesthesia and pain medicine: JDAPM, 2024)
Concomitant chemoradiotherapy (CCRT) treated patients experience various complications. We present a rare case of post-CCRT Bell's palsy and describe its various possible causes, so as to increase awareness among clinicians about Bell's palsy being a CCRT-associated adverse effect. The patient was a 48-year-old man diagnosed with squamous cell carcinoma who presented with post-CCRT Bell's palsy. After radiotherapy for 6 weeks (overall 67.5 Gy) and four rounds of cisplatin chemotherapy, he complained of paralysis of the entire left face. A test was performed 33 days after the last CCRT session to differentiate Bell's palsy from other causative factors. Based on magnetic resonance imaging findings, facial nerve invasion due to tumor size increase was determined to not cause Bell's palsy. Inflammation of the left Eustachian tube was observed. Hence, steroids and famciclovir were administered, which markedly improved the facial paralysis symptoms within 56 days after facial paralysis development. In conclusion, patients can develop Bell's palsy owing to complex effects of various CCRT mechanisms. Although the exact cause of Bell's palsy has not been identified and the effectiveness of drug treatment was questionable in this case, unlikely causative factors should be excluded through various tests and appropriate and timely measures must be adopted.